2018
DOI: 10.1002/jcb.27678
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits breast cancer cell invasion through modulating DJ‐1/KLF17/ID‐1 signaling pathway

Abstract: Breast cancer is the most common neoplastic disorder diagnosed in women.The main goal of this study was to explore the effect of melatonin against breast cancer metastasis and compared this with the actions of taxol (a well-known chemotherapeutic drug), and the impact of their combination against breast cancer metastasis. Melatonin showed no cytotoxic effect while taxol showed antiproliferative and cytotoxic effects on MCF-7 and MDA-MB-231 cells.Furthermore, melatonin inhibited the generation of reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
2
16
0
1
Order By: Relevance
“…Thus, more detailed molecular studies need to be conducted to reveal the mechanisms involved in CRC metastasis to promote the development of an early intervention for high-risk cases involving metastasis. Numerous studies have indicated that DJ-1 is a key modulator of metastasis in various types of cancer (22,23). The current results revealed that DJ-1 expression increased in CRC, and levels were closely related to the pathological features of the P9 disease.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, more detailed molecular studies need to be conducted to reveal the mechanisms involved in CRC metastasis to promote the development of an early intervention for high-risk cases involving metastasis. Numerous studies have indicated that DJ-1 is a key modulator of metastasis in various types of cancer (22,23). The current results revealed that DJ-1 expression increased in CRC, and levels were closely related to the pathological features of the P9 disease.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, the role of DJ-1 in mitochondrial metabolic function is modulated by 14-3-3β. DJ-1 modulation of this novel molecular mechanism of mitochondrial metabolic efficiency is potentially involved in promoting the proliferation of cancer cells (24).DJ-1 enhances tumor metastasis and invasion via activation of the PLAGL2/Wnt/BMP4 axis in CRC (22). In addition, DJ-1 activates the pKB/ Akt signaling pathway by inhibiting PTEN, thereby promoting the progression of ovarian, lung, and breast cancer (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel exerts anticancerous and antimetastatic effects at low concentration in both hormone‐dependent MCF‐7 and hormone‐independent MDA‐MB‐231 breast cancer cells. Paclitaxel suppresses invasion and migration by decreasing the mesenchymal gene snail and increasing epithelial gene E‐cadherin as well as decreasing DJ‐1 and ID‐1 with a simultaneous increase in KLF17 expression at the mRNA levels (El‐Sokkary, Ismail, & Saber, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…This applies both to different types of cancer, 7,10-15 including breast cancer. 8,16 and other invasive pathological processes unrelated to cancer, such as ademyosis or endometriosis. 17,18 Melatonin can inhibit different cell signaling pathways involved in carcinogenesis, which can explain its relative versatility, underlying its action against different types of cancer.…”
Section: Melatoninmentioning
confidence: 99%
“…For example, melatonin inhibits proliferation and invasion of glioma cells via repression of miRNA-155, 14 modulates tumor growth in PTEN-mutated gliomas, 11 inhibits the proliferation of gastric cancer cells through regulating the miR-16-5p-Smad3 pathway 13 and inhibits breast cancer cell invasion through modulating DF-1/KLF17/ID-1 signaling pathway. 8 Hormonal replacement therapy improves quality of life and prevents several serious diseases in women with premature or physiological menopause. At the same time, it is a factor increasing the risk of carcinogenesis, especially concerning breast cancer.…”
Section: Melatoninmentioning
confidence: 99%